Respostas

2014-03-13T14:30:43-03:00
C=  a11 a12 a13
     a21  a22 a23
     a31 a32 a33                              i+j se i=j                              -i-j se ifor diferente de j
                                                     a11 -> 1+1=2                          a12 -> -1-2 = -3
                                                     a22 -> 2+2=4                          a13-> -1-3= -4
                                                     a33 -> 3+3=6                           a21-> -2-1= -3
                                                                                                   a23 -> -2-3=  -5
                                                                                                   a31 -> -3-1 = -4
                                                                                                   a32->  -3-2= -5
C=  2  -3  -4
     -3  4    -5
     -4  -5   6 

1 5 1